MAINTAINING OBJECT AND QUERY RESULT CONSISTENCY IN A TRIPLESTORE DATABASE (2012)
A database management data processing system has been provided. The system can include a host computing system that includes at least one server with memory and at least one processor. The system further includes a database coupled to the host computing system and a database management system (DBMS) executing in the host computing system and managing access to the database through a statement table implemented as a triplestore. Finally, the system includes a triplestore management module coupled to the DBMS. The module includes program code enabled to retrieve from the triplestore a record for a number of rows provided for a common subject in order to validate consistency of data read from the statement table for the particular subject.